2013
DOI: 10.4025/actasciagron.v35i2.16166
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of leaf aqueous extract of Rapanea umbellata (Mart.) Mez (Primulaceae) on weeds

Abstract: ABSTRACT. Allelopathic substances can be used to develop weed control alternatives based on natural products. The objective of this study was to compare the phytotoxic activity of aqueous leaf extracts of Rapanea umbellata with the toxicity of a synthetic herbicide on the germination and growth of weed species. The weeds species barnyard grass (Echinochloa crus-galli), wild poinsettia (Euphorbia heterophylla) and morning glory (Ipomoea grandifolia) were used. The effects of the aqueous leaf extract of R. umbel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It indicates more tolerance to allelochemical extract as there was minimum damage to metabolically active tissues. Barkosky et al, (2000), Chai et al (2013) and Novaes et al (2013) reported similar findings.…”
Section: Discussionmentioning
confidence: 52%
“…It indicates more tolerance to allelochemical extract as there was minimum damage to metabolically active tissues. Barkosky et al, (2000), Chai et al (2013) and Novaes et al (2013) reported similar findings.…”
Section: Discussionmentioning
confidence: 52%
“…As observed by Keszei et al (2008), this family is known for the elevated concentration of terpenes in their leaves and for the strong qualitative and quantitative variation of such compounds among the taxon, populations and individuals. The results published by Imatomi et al (2013a) do not indicate grouping of bioactivity for the 15 studied species by a taxonomic approach. The most studied Myrtaceae genera were Eugenia L. (6 occurrences), Myrcia D.C. (5 occurrences), Psidium L. (4 occurrences) and Stryphnodendron Mart.…”
Section: Plant Familiesmentioning
confidence: 73%
“…In all cases, tests were carried out on leaf extracts. Of the 15 species studied by Imatomi et al (2013a), 12 showed activity. Blepharocalyx salicifolius Kuth O. Berg, Psidium australe Cambess., Eugenia punicifolia (Kunth) DC., Myrcia multiflora DC.…”
Section: Allelopathic Activitymentioning
confidence: 99%
“…The neotropical Brazilian savanna is of great interest from the chemical ecology (allelopathy) point of view, because this ecosystem has a marked seasonal climate [10], and the species grow in nutritionally poor soils [11]. Furthermore, very few studies have been carried out on the isolation, identification, and potential of secondary metabolites from plants of the Cerrado [12] [13].…”
mentioning
confidence: 99%
“…Mez (Myrsinaceae) is an arboreal, evergreen species that grows in the Cerrado [16]. Recent preliminary studies on extracts from leaves, stems, and roots indicated that only R. umbellata leaves showed phytotoxic effects on infesting species [13]. This finding suggests an allelopathic interaction.…”
mentioning
confidence: 99%